Strain Identification of Trichophyton rubrum by Specific Amplification of Subrepeat Elements in the Ribosomal DNA Nontranscribed Spacer - Jackson, Colin J. (American Society for Microbiology, 2000)
Trichophyton rubrum is the commonest cause of dermatophytosis of skin and nail tissue. Molecular characterization of the T. rubrum ribosomal DNA nontranscribed-spacer region revealed two novel tandemly repetitive subelements (TRSs): TRS-1, containing a 27-bp palindromic sequence, and TRS-2. Specific amplification of TRS-1 produced strain-characteristic banding patterns (PCR types), with 21 TRS-1 PCR types recognized from 101 clinical isolates. Four simple patterns representing 1 to 4 copies of TRS-1 accounted for 75 (75%) of all 101 strains, whereas more complex patterns were observed for 21 (20%) of the 101 isolates. The copy number of TRS-2 was 0 to 3 repeats per cistron, with a majority of isolates having two copies of this element. Eleven isolates were polymorphic for TRS-2, and in combination, 23 separate PCR types were recognized by amplification of both TRS-1 and TRS-2. The PCR patterns from both elements were stable and reproducible. Elements with homology to TRS-1 were present in three phylogenetically related species, Trichophyton violaceum, Trichophyton gourvilii, and Trichophyton soudanense, but these elements were not identified in other dermatophyte taxa. There was no clear correlation of PCR type with specimen (skin or nail tissue), but certain PCR types appeared to show a bias in geographic distribution. This new method of typing T. rubrum will enable important questions about pathogenesis and epidemiology of this fungus to be addressed.